Good Timing in the Cell Cycle for Precise DNA Repair by BRCA1 - Durant, Stephen T.; Nickoloff, Jac A (Cell cycle (Georgetown, Tex.), 2005)
It is now clear that large DNA-binding proteins have evolved in mammals to orchestrate the relatively ancient processes of DNA recombinational repair. These proteins are recruited to accurately repair DNA double-strand breaks (DSBs) - the frequent, potentially lethal and mutagenic lesions in the genomes of all organisms. An essential mammalian regulator of DSB repair is BRCA1. Heterozygous BRCA1 mutations predispose individuals to breast, ovarian and other secondary cancers. BRCA1-defective cells exhibit reduced DSB repair, sensitivity to a wide range of DNA damaging agents, genomic instability and defects in the S-phase checkpoint, transcription and chromatin remodelling. DSBs can be repaired by Rad51/RPA-dependent homologous recombination (HR) or DNA-PK-dependent non-homologous end-joining (NHEJ). Both of these pathways can be imprecise and mutagenic. BRCA1 plays a central role in promoting accurate repair by both HR and NHEJ. Consistent with recent evidence, we have assembled a novel cell-cycle-dependent model in which DNA-PK inhibits RPA in S-phase of the cell cycle, while BRCA1 inhibits the exonuclease processivity of the MRE11/RAD50/NBS1 (MRN) complex and facilitates the removal of RPA in S and G2 phase. This model provides an explanation for how BRCA1 promotes accurate DSB repair during various phases of the cell cycle and also accounts for the dual effects that BRCA1 and MRN activity have upon DNA repair and S-phase arrest.